Analgesic effect of Sansevieria longiflora (Sim) water extract and xylocaine cream on surgical wound incision in rats - Kilani, MA; Hassan, AZ; Fadason, ST; Abidoye, EO; Oladimeji, LO; Obalowu, AM; Kilani, HM Badmus (Bangladesh Journal of Scientific and Industrial Research, 2020)
Analgesic effect of Sansevieria longiflora (S. longiflora) on surgically created wound was studied. Phytochemical screening of the crude water extracts was carried out following standard procedures. Sansevieria longiflora leaves was heated and the sap was squeezed into a sample bottle to be used as it was traditional believed. Its water extract was also prepared following standard procedure. Four (4) albino rats consisting of 2 males and 2 females were used for the study. One centimeter full thickness skin incision was created on 4 different locations at the dorsal region of each rat under anaesthesia. Each of the 4 wounds created was topically treated once daily with S. longiflora sap (E), S. longiflora water extract (F), Physiological saline solution (C) and xylocaine cream (G). The treatment regimen was rotated in a clockwise direction on each rat. Pain perception was evaluated with an algometer at 6:00 GMT (morning) and 18:00 GMT (evening) from day 1 post surgery for 5 days. The phytochemical studies revealed that S. longiflora contains carbohydrates, glycoside, saponins, steroids, triterpenes, flavonoids, alkaloids and tannins. Day1 after the surgery, the mean morning value of force (N) required to elicit pain in xylocaine treated wounds (5.2 ± 0.79) were significantly higher (p<0.001) than that of physiological saline solution (2.8 ± 0.29) whereas, not different from that of S. longiflora sap (4.48 ± 0.57) and water extract (4.2 ± 0.6). Similarly, on the day 5 after the surgery, the mean morning value of force (N) required to elicit pain in xylocaine treated wounds were significantly higher (p<0.0001) than that of physiological saline solution (PSS) treated wounds and not different from that of S. longiflora sap and water extract. This showed that S. longiflora sap and water extract possess analgesic effect on incisional wounds. This study serves as a preliminary study on this plant towards searching for potent analgesics that could be used for procedural pain management. Bangladesh J. Sci. Ind. Res.55(2), 99-106, 2020